2016
DOI: 10.1371/journal.pone.0150999
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Sources of Heterogeneity in Randomized Controlled Trials of the Effects of Pharmacist Interventions on Glycemic Control in Type 2 Diabetic Patients: A Systematic Review and Meta-Analysis

Abstract: ObjectiveTo assess the effect of pharmacist interventions on glycemic control in type 2 diabetic patients and to examine factors that could explain the variation across studies.MethodsA comprehensive literature search was performed in PubMed, Scopus, and LILACS databases for randomized controlled trials (RCTs) published up to July 2015. The search strategy included the use of MeSH terms or text words related to pharmacist interventions, type 2 diabetes, and randomized controlled trials. RCTs published in Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 51 publications
7
45
0
13
Order By: Relevance
“…These meta‐analyses included different practice settings, severity of disease and components of pharmacist interventions; then, we believe that there may be an effect size difference compared with our diabetes outpatient clinic. In addition, a multiple regression analysis indicated that our pharmacist‐physician collaborative care model was more effective for patients with poor glycemic control, which is similar to findings of recent meta‐analysis on pharmacist interventions for patients with diabetes .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These meta‐analyses included different practice settings, severity of disease and components of pharmacist interventions; then, we believe that there may be an effect size difference compared with our diabetes outpatient clinic. In addition, a multiple regression analysis indicated that our pharmacist‐physician collaborative care model was more effective for patients with poor glycemic control, which is similar to findings of recent meta‐analysis on pharmacist interventions for patients with diabetes .…”
Section: Discussionsupporting
confidence: 81%
“…Randomized controlled trials have shown a positive impact of interventions delivered by pharmacists in collaboration with physicians on glycemic control in outpatients with type 2 diabetes . However, most clinical trials were carried out in developed countries and interventions and study design were poorly described ; this may hamper the implementation of the conducted clinical pharmacy services into others realities, the mapping the components of the pharmacist interventions and measure their actual effects. Besides, studies on pharmacist interventions have focused primarily on outcomes reporting and usually do not provide useful insights into factors that make an intervention successful in achieving outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…High heterogeneity values negatively contribute to the strength of the evidence . Investigating the sources of heterogeneity is a prerequisite to demonstrating the impact of pharmacists' interventions . Several attempts were made to enhance the quality of the description of the components of pharmacists' interventions …”
Section: Discussionmentioning
confidence: 99%
“…Also, combining pharmacological and behavioural strategies may incrementally (or perhaps even synergistically) increase effectiveness [34]. However, the effect sizes observed were modest when compared to the general population [18, 78], suggesting that tailored interventions which address the specific challenges faced by people with SMI are needed.…”
Section: Discussionmentioning
confidence: 99%
“…We also conducted univariate random effects meta-regression using mean HbA 1c or fasting glucose at baseline to explore whether or not this explained some of the heterogeneity among studies [18]. …”
Section: Methodsmentioning
confidence: 99%